Day 2 Tue, November 14, 2017 2017
DOI: 10.2118/188187-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sequenced Fracture Degradable Diverters Improve Efficiency of Acid Fracturing in Multiple Perforated Intervals Completion Assembly

Abstract: Gas-bearing carbonate reservoirs in moderate to low permeability reservoirs have been targets for acid fracturing treatments in the Middle East. These formations typically exhibit high temperatures, medium to low porosity, and high heterogeneity in terms of lithology and reservoir properties. The heterogeneity dictates completion strategy, with multiple perforated intervals across large gross height in vertical wells with subsequent acid fracturing treatments that aim to cover all perforated intervals in a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…To validate the model, it was compared to an acid fracture job performed on a laminated formation. Rahim et al provided a temperature profile after an acid-fracturing job in a Middle Eastern laminated formation. They showed the lithology distribution where a calcite layer existed in the middle of a dolomite pay zone.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the model, it was compared to an acid fracture job performed on a laminated formation. Rahim et al provided a temperature profile after an acid-fracturing job in a Middle Eastern laminated formation. They showed the lithology distribution where a calcite layer existed in the middle of a dolomite pay zone.…”
Section: Model Validationmentioning
confidence: 99%
“…Carbonate formations are normally heterogeneous and in many cases contain both calcite and dolomite minerals that are sequentially laminated . Because of differences in reactivity and stress, acid preferentially etches the calcite layers and leaves the dolomite layers understimulated.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple publications on improving the acid fracturing efficiency in naturally fractured reservoirs, many of which focus on using viscoelastic acid systems with diverters to reduce the acid loss form the main fractures by bridging the natural fractures (Rahim et al 2017;Williams et al 2016;McCartney et al 2017). However, the effect of natural fractures on the efficiency of the acid fracturing treatment and created fracture conductivity is not fully understood.…”
Section: Background and Motivation Of The Studymentioning
confidence: 99%
“…Gdanski (1993) studied experimentally the fluid loss control during acid fracturing and concluded that acid leakoff can be significantly reduced by using solids for plugging and bridging wormholes. Rahim et al (2017) presented results for successful application of degradable multi-modal particulate diverters mixed with fibers to enhance the leakoff control in near wellbore region and to improve the efficiency of acid fracturing treatment in heterogeneous formation. Williams et al (2016) conducted an experimental study on improving the acid leakoff control by using far-field solid particulate diverters which effectively bridge wormholes and hairline fractures away from the wellbore region.…”
Section: Acid Fracturing Stimulation Overviewmentioning
confidence: 99%